Method for ether-promoted growth of nickel hydroxide nanosheets on nickel surface, material and application thereof

CN117987843BActive Publication Date: 2026-10-30DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211363884.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-02
Publication Date
2026-10-30
Estimated Expiration
2042-11-02

AI Technical Summary

Technical Problem

此方法制备周期长,且制备条件的影响因素不方便可控

Benefits of technology

[0015]采用一步法,将泡沫镍基底浸没于含有氯铂酸的醚的酸性溶液中,在较低温度下进行热处理,无需额外加入镍离子盐的情况下,于泡沫镍表面原位生长了修饰有铂纳米颗粒的氢氧化镍纳米片混合材料。本发明无须传统水热法的高温和高压的制备条件,对设备要求低,无须额外加入镍离子盐,依靠质子酸的氧化能力,无须依靠空气中的氧气自然缓慢溶解和氧化使得金属镍氧化成镍离子,制备互相交接的氢氧化镍纳米片阵列,为铂颗粒的分散提供了大的比表面积,因此铂/氢氧化镍混合材料具有丰富的活性位点和孔道结构,有利于得到贵金属负载量低、活性和稳定性高的混合材料,也为原位制备高性能、稳定的电极提供了指导,在能源、催化等领域具有广泛的应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117987843B_ABST
    Figure CN117987843B_ABST
Patent Text Reader

Abstract

The application provides a method for promoting growth of nickel hydroxide nanosheets on a nickel surface by using an ether. In the method, a nickel foam substrate is immersed in an acidic solution containing chloroplatinic acid and ether, and is subjected to heat treatment at a low temperature, so that a nickel hydroxide nanosheet mixed material decorated with platinum nanoparticles is grown in situ on the surface of the nickel foam without adding nickel ion salt additionally. The platinum / nickel hydroxide / nickel foam electrode prepared by the method exhibits excellent hydrogen production activity in the reaction of hydrogen production by alkaline electrolysis of water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of nanomaterials, and specifically relates to a method for preparing nickel hydroxide nanosheets in situ on the surface of metallic nickel. Background Technology

[0002] The rapid depletion of traditional fossil fuels and the increasing demand for energy necessitate adjustments to society's energy structure and the development of clean and renewable energy sources to reduce dependence on fossil fuels (Chemical Reviews, 2020, 120: 851-918). Hydrogen, an energy carrier whose combustion product is water, is one of the most promising energy sources. Currently, the most widely recognized green and sustainable method for hydrogen production is water electrolysis, which can achieve "zero carbon emissions" (Nature Reviews Chemistry, 2017, 1: 0003). Platinum remains the best-performing electrocatalyst for water electrolysis, but its high price and slow rate of water cracking limit its activity under alkaline conditions (Nano Energy, 2019, 58: 167-174). Therefore, preparing platinum-based metal materials with low loading and high water dissociation activity is one of the keys to improving the activity of alkaline water electrolysis for hydrogen production and reducing the cost of industrial applications (Nature Energy, 2019, 4(6): 512-518).

[0003] Transition metal hydroxides, such as nickel hydroxide, can efficiently promote water splitting, but their ability to adsorb and desorb active hydrogen to produce hydrogen is relatively weak. Constructing a hybrid material of platinum metal and nickel hydroxide can improve the electrolytic hydrogen production activity of platinum-based materials while reducing the amount of platinum required (Small Methods, 2020, 4:1900796). Markovic et al. (Science, 2011, 334: 1256-1260) deposited nanoscale nickel hydroxide clusters on a platinum electrode and found that its catalytic alkaline water electrolysis hydrogen production activity was 8 times higher than that of a pure platinum electrode. In the patent publication CN107954483A, "An α-phase nickel hydroxide ultrathin nanosheet and its preparation method," the preparation method of α-phase nickel hydroxide nanosheets involves mixing an ethanol solution of a soluble nickel salt with an ethanol solution of urea, then adding propylene glycol and stirring until homogeneous. The precursor solution is then subjected to a solvothermal reaction at 110-130 °C for 6-10 h. This process involves high temperatures and long durations, and the prepared nickel hydroxide powder needs to be fixed to the electrode with a binder, which may increase the charge transfer resistance of the electrode, and the active material is prone to detachment. In patent CN112080756A, entitled "A Hydrogen Evolution Electrode and Its Preparation and Application," the foamed nickel substrate is placed in an acidic solution containing nickel ions to convert the added nickel ions into nickel hydroxide, and then placed in a chloroplatinic acid solution to deposit platinum particles. In patent CN110040792A, entitled "A Method for Preparing Nickel Hydroxide Nanosheet Array Material Grown on the Surface of Foamed Nickel," the foamed nickel is cleaned and soaked in an acid solution, then immersed in deionized water. Through oxygen corrosion for 2-5 days, the surface nickel is oxidized to form nickel hydroxide through the natural slow dissolution and oxidation of atmospheric oxygen. This method has a long preparation cycle, and the influencing factors of the preparation conditions are not easily controllable.

[0004] The self-supporting ternary composite electrode (platinum / nickel foam / nickel hydroxide) is a highly efficient electrode for alkaline water electrolysis to produce hydrogen. This invention utilizes a simple process, employing nickel foam as both the nickel source and substrate, to prepare nickel hydroxide nanosheets grown on the nickel surface via ether-promoted growth. Taking nickel foam as an example, it is placed in an acidic ether solution containing chloroplatinic acid precursor. Under the coordination induction of the ether, the protic acid in the solution oxidizes the metallic nickel on the surface of the nickel foam into nickel ions. During the hydrolysis of hydrated nickel ions, secondary acidic protons repeatedly act, eliminating the need for oxygen oxidation, resulting in the rapid growth of nickel hydroxide on the nickel foam surface and the simultaneous deposition of platinum nanoparticles. This method allows for the in-situ preparation of a platinum / nickel hydroxide / nickel foam electrode material with high activity for alkaline water electrolysis to produce hydrogen under relatively mild conditions and in a short time. It reduces the amount of precious platinum used, provides mild conditions, and simplifies the process, facilitating large-scale production. Summary of the Invention

[0005] The purpose of this invention is to provide a method for promoting the growth of nickel hydroxide nanosheets on a nickel surface using ether. Under the coordination induction of ether, metallic nickel on the surface of nickel foam is oxidized to nickel ions by a protic acid in solution. During the hydrolysis of hydrated nickel ions, secondary acidic protons repeatedly act, eliminating the need for oxygen oxidation. This allows for the rapid growth of nickel hydroxide on the nickel foam surface in a short time, while simultaneously depositing platinum nanoparticles. This invention provides an in-situ preparation of a platinum / nickel hydroxide / nickel foam electrode material with high activity for alkaline water electrolysis to produce hydrogen under relatively mild conditions.

[0006] A method for promoting the growth of nickel hydroxide nanosheets on a nickel surface using ether involves placing metallic nickel in an acidic ether solution containing a precursor of another metal ion and heating it to obtain nickel hydroxide nanosheets immobilized on the surface of the metallic nickel.

[0007] The ethers include, but are not limited to, one or more of ether-based compounds; including, but not limited to, one or more of glycol ether-based compounds; preferably, including, but not limited to, one or more of ethylene glycol ether and propylene glycol ether-based compounds.

[0008] The ethers mentioned include, but are not limited to, one or more of ethylene glycol monomethyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, propylene glycol dimethyl ether, diethylene glycol diethyl ether, and n-butyl ether.

[0009] The ether solution is composed of ether, alcohol, and water. Their volume ratio is (2:7:1)-(5:2:3); the pH value of the acidic ether solution is 1-6; the pH value of the solution is adjusted using 1-3 mol / L hydrochloric acid, 1-3 mol / L sulfuric acid, or 1-3 mol / L nitric acid. The alcohol compounds comprising the solution include, but are not limited to, one or a mixture of two or more of methanol, ethanol, propanol, isopropanol, butanol, ethylene glycol, and glycerol.

[0010] The other metal precursor includes one or more of transition metals and platinum group elements, including but not limited to one of copper, zinc, tin, ruthenium, rhodium, palladium, osmium, iridium, gold, and silver, and the reduction potential of the other metal is higher than that of nickel.

[0011] The other metal precursor mentioned includes, but is not limited to, chlorides, nitrates, and carbonates, such as chloroauric acid, potassium chloroaurate, sodium chloroaurate, ammonium chloroaurate, chloroplatinic acid, sodium chloroplatinate, potassium chloroplatinate, platinum chloride, potassium chloroplatinate, sodium chloroplatinate, diethylamine platinum chloride, platinum nitrate, ammonium tetrachloroplatinate, ammonium chloropalladium, sodium chloropalladium, potassium chloropalladium, ammonium chlororhodium, sodium chlororhodium, potassium chlororhodium, iridium, sodium chloroiridium, potassium chloroiridium, rhodium trichloride, ruthenium trichloride, cupric chloride, and cuprous chloride, or two or more of these.

[0012] The nickel metal mentioned includes, but is not limited to, reduced nickel metal of different morphologies and sizes, such as nickel foam, nickel mesh, Raney nickel, or nickel powder.

[0013] The temperature range of the heating process is 25-200 °C, preferably 80-100 °C; the time is 1-4 hours.

[0014] The platinum / nickel hydroxide / nickel foam ternary composite electrode prepared by this method exhibits excellent activity and stability as a hydrogen evolution electrode for water electrolysis to produce hydrogen under alkaline conditions.

[0015] A one-step method was employed, in which a nickel foam substrate was immersed in an acidic solution of ether containing chloroplatinic acid and heat-treated at a relatively low temperature. This resulted in the in-situ growth of a nickel hydroxide nanosheet hybrid material modified with platinum nanoparticles on the nickel foam surface without the need for additional nickel ion salts. This invention eliminates the high temperature and high pressure requirements of traditional hydrothermal methods, requiring less sophisticated equipment. It utilizes the oxidizing power of protic acids, avoiding the need for the slow, natural dissolution and oxidation of metallic nickel to nickel ions by atmospheric oxygen, to prepare an array of interconnected nickel hydroxide nanosheets. This provides a large specific surface area for the dispersion of platinum particles. Therefore, the platinum / nickel hydroxide hybrid material possesses abundant active sites and a porous structure, which is beneficial for obtaining a hybrid material with low noble metal loading and high activity and stability. It also provides guidance for the in-situ preparation of high-performance, stable electrodes, showing broad application prospects in energy, catalysis, and other fields. Attached Figure Description

[0016] Figure 1 This is a scanning electron microscope image of nickel hydroxide nanosheets with platinum particles immobilized on the surface of the nickel foam prepared in Example 1.

[0017] Figure 2 This is an X-ray diffraction image of nickel hydroxide nanosheets with platinum particles grown and immobilized on the surface of the nickel foam prepared in Example 1.

[0018] Figure 3 This is a transmission electron microscope image of nickel hydroxide nanosheets immobilized with platinum particles prepared in Example 1.

[0019] Figure 4 This is a high-resolution transmission electron microscope image of nickel hydroxide nanosheets immobilized with platinum particles prepared in Example 1.

[0020] Figure 5 This is a high-resolution transmission electron microscope image of nickel hydroxide nanosheets immobilized with platinum particles prepared in Example 1.

[0021] Figure 6The polarization curves are for the electrolysis of water to produce hydrogen using the electrodes prepared in Examples 1, 2, and 3 and the pure nickel foam substrate in 1.0 M KOH solution.

[0022] Figure 7 This is a scanning electron microscope image of the surface of the control sample nickel foam prepared in Example 2.

[0023] Figure 8 This is a scanning electron microscope image of the surface of the control sample nickel foam prepared in Example 3. Detailed Implementation

[0024] The following example, illustrating the growth of nickel hydroxide nanosheets on the surface of nickel foam in a chloroplatinic acid solution of ethylene glycol diethyl ether, provides a more detailed description of the invention. The scope of protection of this patent is not limited to the specific embodiments, but is limited by the claims. Example 1

[0025] Preparation of platinum / nickel hydroxide / nickel foam composite electrode: A nickel foam sheet with a pore size of 0.1 mm, a porosity of 97.2%, and a thickness of 0.1 mm (length × width = 1 cm × 2 cm) was immersed in a sample tube containing 7 ml of chloroplatinic acid solution (3.2 ml ethanol, 3.1 ml ethylene glycol diethyl ether, and 0.7 ml water; the amount of chloroplatinic acid added was calculated based on a theoretical platinum mass loading of 1%, and the solution pH was 2.5). The electrode was kept in an 80 °C water bath for 4 h. After cooling to room temperature, the electrode was washed with ethanol and water and dried in a 40 °C vacuum oven for 2 h.

[0026] Figure 1 The image shows a scanning electron microscope image of nickel hydroxide nanosheets on the surface of the nickel foam prepared in this embodiment. It shows a dense morphology of nanosheets growing perpendicular to the surface of the nickel foam and intersecting (or crossing) each other. The thickness of the layers formed by the intersecting nanosheets (i.e., the nanosheet layers formed by the nanosheets stacked one after another) is 100-3000 nm, the thickness of the nanosheets is 20-200 nm, and the distance between the two farthest points on the surface of the nanosheets is 200-2000 nm.

[0027] Figure 2 The image shows an X-ray diffraction pattern of nickel hydroxide nanosheets on the surface of the nickel foam prepared in this embodiment. Compared with the standard card (JCPDS 00-003-0117), the two signals at 33.5 ° and 38.8 ° are attributed to the characteristic diffraction peaks of β-nickel hydroxide, confirming that the nanosheets are β-phase nickel hydroxide.

[0028] Figure 3 The image shown is a transmission electron microscope image of the nickel hydroxide nanosheets prepared in this embodiment, which shows the morphology of the ultrathin nickel hydroxide nanosheets.

[0029] Figure 4 The image shows a high-resolution transmission electron microscope image of nickel hydroxide nanosheets with platinum nanoparticles immobilized on them, prepared in this embodiment. The image shows that platinum nanoparticles are embedded on the surface of the nickel hydroxide nanosheets, and the particles are highly dispersed and have a relatively uniform particle size (average particle size of about 2.2 nm, particle size distribution range of 1-10 nm).

[0030] Figure 5 The images are high-resolution transmission electron microscope images of nickel hydroxide nanosheets with platinum nanoparticles immobilized in this embodiment. The interplanar spacings of 0.226 nm and 0.232 nm correspond to the (111) crystal plane of the platinum particles and the (101) crystal plane of the nickel hydroxide, respectively, confirming that the nanoparticles present on the surface of the nickel hydroxide are platinum.

[0031] Figure 6 The polarization curves of the electrolysis of water to produce hydrogen in 1.0 M KOH solution are shown in the figure. Using the electrode prepared in this embodiment as the working electrode, a carbon rod as the counter electrode, and Hg / HgO as the reference electrode, the polarization curves are obtained. As can be seen from the figure, under the same current density, the platinum / nickel hydroxide / nickel foam electrode prepared in this embodiment exhibits better polarization at a current density of 200 mA / cm². 2 At that time, its hydrogen evolution overpotential was only 109mV, which is the lowest overpotential, indicating that it has the lowest energy consumption and high activity in hydrogen production by water electrolysis.

[0032] Example 2 (Comparative example, the solvent for the chloroplatinic acid solution is ethanol and water, without ethylene glycol diethyl ether) Similar to the preparation of the platinum / nickel hydroxide / nickel foam composite electrode, the difference lies in the absence of ethylene glycol diethyl ether in the chloroplatinic acid solution. A nickel foam sheet with a pore size of 0.1 mm, a porosity of 97.2%, and a thickness of 0.1 mm (length × width = 1 cm × 2 cm) was immersed in a sample tube containing 7 ml of chloroplatinic acid solution (6.3 ml of ethanol and 0.7 ml of water; the amount of chloroplatinic acid added was calculated based on a theoretical platinum mass loading of 1%, and the solution pH was 2.5). The solution was kept in an 80 °C water bath for 4 h. After cooling to room temperature, the electrode was washed with ethanol and water and dried in a 40 °C vacuum oven for 2 h.

[0033] Figure 7 The images are scanning electron microscope (SEM) images of the surface of the comparative sample, nickel foam, prepared in this embodiment. They show granular material on the surface of the nickel foam, with particle sizes ranging from 50-500 nm, possibly platinum particles or nickel compounds. No nanosheet morphology was observed in the images, indicating that nickel hydroxide nanosheets would not grow without ethylene glycol diethyl ether in the preparation solution. Figure 6 It can be seen that the catalytic activity of the electrode prepared in this embodiment for alkaline water electrolysis to produce hydrogen is lower than that of the electrode prepared in Example 1, at a current density of 200 mA / cm².2 At that time, its hydrogen evolution overpotential was 143 mV, requiring a higher voltage to achieve the hydrogen evolution performance of the electrode prepared in Example 1, thus increasing energy consumption.

[0034] Example 3 (Comparative example, the solvent for the chloroplatinic acid solution is water, without ethylene glycol diethyl ether and ethanol) Similar to the preparation of the platinum / nickel hydroxide / nickel foam composite electrode, the difference lies in the absence of ethylene glycol diethyl ether and ethanol in the chloroplatinic acid solution. A nickel foam sheet with a pore size of 0.1 mm, a porosity of 97.2%, and a thickness of 0.1 mm (length × width = 1 cm × 2 cm) was immersed in a sample tube containing 7 ml of chloroplatinic acid aqueous solution (7 ml water, the amount of chloroplatinic acid added calculated based on a theoretical platinum mass loading of 1%, solution pH 2.6), and kept in an 80 °C water bath for 4 h. After cooling to room temperature, the electrode was washed with ethanol and water and dried in a 40 °C vacuum oven for 2 h.

[0035] Figure 8 The images are scanning electron microscope (SEM) images of the surface of the comparative sample, nickel foam, prepared in this embodiment. They show particles and irregularly shaped aggregates of these particles on the surface. The particle size is 100-1000 nm, and the length of the irregular aggregates is 500-5000 nm. No nanosheet morphology was observed in the images, indicating that nickel hydroxide nanosheets will not grow under mild conditions in pure aqueous solution within a certain time. Figure 6 It can be seen that the catalytic activity of the electrode prepared in this embodiment for alkaline water electrolysis to produce hydrogen is lower than that of the electrode prepared in Example 1, at a current density of 200 mA / cm². 2 At that time, its hydrogen evolution overpotential was 149 mV. A higher voltage was required to achieve the hydrogen evolution performance of the electrode prepared in Example 1, which increased energy consumption and cost.

[0036] As demonstrated by the above examples, a simple one-step method allows for the in-situ growth of nickel hydroxide nanosheets immobilized with platinum particles on nickel foam in the presence of ethylene glycol diethyl ether solution. In the comparative example without ethylene glycol diethyl ether, nickel hydroxide nanosheets do not grow on the surface of the nickel foam. Compared to the nickel foam electrode without nickel hydroxide prepared in the comparative example, the prepared platinum / nickel hydroxide / nickel foam electrode exhibits better hydrogen evolution performance in the alkaline water electrolysis reaction.

[0037] This invention provides a method for ether-promoted growth of nickel hydroxide nanosheets on a nickel surface. Using a one-step method, a nickel foam substrate is immersed in an acidic solution of ether containing chloroplatinic acid and subjected to heat treatment at a relatively low temperature. Without the need for additional nickel ion salts, a mixed material of nickel hydroxide nanosheets modified with platinum nanoparticles is grown in situ on the surface of the nickel foam. The platinum / nickel hydroxide / nickel foam electrode prepared by this method exhibits excellent hydrogen production activity in alkaline water electrolysis for hydrogen production, showing broad application prospects in energy, catalysis, and other fields. This invention eliminates the high temperature and high pressure preparation conditions of traditional hydrothermal methods and the need for additional nickel ion salts. Utilizing the assisted effect of ether, an array of interconnected nickel hydroxide nanosheets is prepared under mild conditions, providing a large specific surface area. Therefore, the platinum / nickel hydroxide mixed material has abundant active sites and a porous structure, which is beneficial for obtaining a mixed material with low noble metal loading, high activity, and high stability. It also provides guidance for the in-situ preparation of high-performance, stable electrodes.

Claims

1. A method for promoting the growth of nickel hydroxide nanosheets on a nickel surface using ether, characterized in that: Nickel metal was placed in an acidic ether solution containing other metal ion precursors besides nickel without additional nickel ion precursors, and heated to obtain nickel hydroxide nanosheets with other metal particles besides nickel immobilized on the surface of the nickel metal. The ether is one or more of ethylene glycol monomethyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, propylene glycol dimethyl ether, diethylene glycol diethyl ether, and n-butyl ether; The acidic ether solution is composed of ether, alcohol and water; their volume ratio is (2:7:1)-(5:2:3); the pH value of the acidic ether solution is 1-6; The alcohols are one or a mixture of two or more of the following: methanol, ethanol, propanol, isopropanol, butanol, ethylene glycol, and glycerol. The metallic nickel is one or more of reduced metallic nickel with different morphologies and sizes, such as nickel foam, nickel mesh, Raney nickel, or nickel powder; The nanosheets are interwoven into layers, that is, the thickness of the nanosheets stacked one after another is 100-3000 nm, the thickness of the nanosheets is 20-200 nm, and the distance between the two farthest points on the surface of the nanosheets is 200-2000 nm. The temperature range of the heat treatment process is 80-100℃; the time is 1-4h.

2. The method according to claim 1, characterized in that: The metals that are not additionally nickel ion precursors include one or more transition metals, namely copper, ruthenium, rhodium, palladium, osmium, iridium, gold, and silver, and the reduction potential of the other metals is higher than that of nickel.

3. The method according to claim 1, characterized in that: The other metal ion precursors besides nickel, which do not contain additional nickel ion precursors, are metal chlorides, nitrates, and carbonates, such as chloroauric acid, potassium chloroaurate, sodium chloroaurate, ammonium chloroaurate, chloroplatinic acid, sodium chloroplatinate, potassium chloroplatinate, platinum chloride, potassium chloroplatinate, sodium chloroplatinate, diethylamine platinum chloride, platinum nitrate, ammonium tetrachloroplatinate, ammonium chloropalladium, sodium chloropalladium, potassium chloropalladium, ammonium chlororhodium, sodium chlororhodium, potassium chlororhodium, iridium, sodium chloroiridium, potassium chloroiridium, rhodium trichloride, ruthenium trichloride, cupric chloride, and cuprous chloride, or two or more of these.

4. A material obtained by the method according to any one of claims 1-3.

5. The application of the material according to claim 4 as a hydrogen evolution electrode in the electrolysis of water under alkaline conditions.

Citation Information

Patent Citations

  • Alpha-phase nickel hydroxide ultrathin nanosheet and preparation method

    CN107954483A

  • Preparation method of nickel hydroxide nanosheet array material growing on surface of foamed nickel

    CN110040792A

  • Reduction state noble metal isolated atom material stable in solution and preparation method thereof

    CN111496265A

  • Hydrogen evolution electrode and preparation and application thereof

    CN112080756A